Agriculture and the Origins of the State in Ancient Egypt. - Allen, R (Elsevier, 1997)
In Egypt, state formation occurred much more rapidly after the adoption of farming than in many other parts of the ancient Near East. Furthermore, the Egyptian state lasted longer and was more stable than most Empires established elsewhere. This paper argues that successful states in the ancient world depended on the ability of elites to extract a surplus from farmers and other producers. This ability was greatest when the population was immobile. The success of the Pharaohs was due to the geography of Egypt--the deserts bordering the Nile meant that habitation was confined to the valley. Farmers could flee tax or rent collectors only along the river. The population control problem was, thus, simpler than elsewhere and was the reason a unified state was created and lasted for millenia. (c) 1997 Academic Press